RECONFIGURING THE EDUCATIONAL PROCESS THROUGH THE USE OF DIGITAL TECHNOLOGIES AND THEIR IMPACT - Alexandra IANCU (Challenges of the Knowledge Society)
In this paper I aim to highlight the profound changes brought to the educational process through the use of digital technologies and the impact they have had during the pandemic and post pandemic period, as the method of computer-assisted instruction and online course delivery is still used today in combination with the traditional method, especially in university settings. In the paper I will analyse the following aspects: (a) European Union policy in the field of digital education; b) The emergence of socio-educational phenomena that have an impact on development such as: the digital divide (digital segregation), digital literacy and computer literacy; c) Changing learning behaviour; d) The effects of using social networks on learners and teachers.